Active Vibration Isolation using Tilt Horizontal Coupling Immune Inertial Double Link Sensor for Low Frequency Applications - Nair, Vishnu G.; Hegde, Navya Thirumaleswar; V., Dileep M. (Journal of Robotics and Control (JRC), 2024)
Addressing the challenge of horizontal tilt coupling is crucial for using inertial sensors in precise applications, such as seismology and seismic isolation, including gravitational wave detection. Researchers have proposed various design solutions, with the Double Link (DL) sensor standing out for its sim- plicity, precision, and effectiveness. This paper explores the use of the DL sensor in an active vibration isolation system. We evaluated different control algorithms, including Proportional- Integral-Derivative (PID), Linear Quadratic Regulator (LQR), Linear Quadratic Gaussian (LQG), and H-infinity. Simulations conducted in the Simscape environment showed that the H-infinity controller performed best, achieving a significant reduction in vibration. While the current study is based on simulations, future work will focus on experimental validation to confirm the system’s practical applicability and robustness in real-world scenarios. Our results demonstrate the potential of the DL sensor and LQG controller to enhance vibration isolation in low-frequency applications. Additionally, we conducted a detailed literature review on various methods used in similar applications. This review highlights alternative approaches, such as other sensor designs and control strategies, and discusses their advantages and limitations.